2009
DOI: 10.1557/mrs2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Crystalline Nanowires

Abstract: Nanowires are among the most exciting one-dimensional nanomaterials because of their unique properties, which result primarily from their chemical composition and large surface area to volume ratio. These properties make them ideal building blocks for the development of next generation electronics, opto-electronics, and sensor systems. In this article, we focus on the unique mechanical properties of nanowires, which emerge from surface atoms having different electron densities and fewer bonding neighbors than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 90 publications
(138 reference statements)
8
126
0
Order By: Relevance
“…The Young's modulus results from our in situ SEM tensile tests agree well with those from the AFM tests. 11,33 The observed size effect on elasticity of Ag NWs is generally a result of their large surface area to volume ratio, 34 more specifically, surface elasticity 35 and/or bulk nonlinear elasticity (due to surface stress). 36,37 Though our results are in good agreement with other experimental results, 11,33 we do note that there is a substantial gap between the experiments and the atomistic simulations in terms of the critical diameter where the elasticity size effect becomes marked.…”
Section: Resultsmentioning
confidence: 99%
“…The Young's modulus results from our in situ SEM tensile tests agree well with those from the AFM tests. 11,33 The observed size effect on elasticity of Ag NWs is generally a result of their large surface area to volume ratio, 34 more specifically, surface elasticity 35 and/or bulk nonlinear elasticity (due to surface stress). 36,37 Though our results are in good agreement with other experimental results, 11,33 we do note that there is a substantial gap between the experiments and the atomistic simulations in terms of the critical diameter where the elasticity size effect becomes marked.…”
Section: Resultsmentioning
confidence: 99%
“…The more pronounced experimentally observed decrease in Ẽ can be due to additional factors such as surface contamination 6,20 and crystal defects. 6,10,20 To address the issue of precision of the pull-in measurements, repeatability and reproducibility experiments were carried out. Figure 4 shows the results for different thicknesses, lengths, and shapes ͑simple and paddle͒, indicating that the pull-in approach is both repeatable for single cantilevers as well as reproducible for different samples.…”
Section: ẽ Tmentioning
confidence: 95%
“…Specifically, various experimental studies on both metallic and semiconducting nanostructures have shown that when the cross-sectional dimension (i.e. diameter) of a nanobeam or nanoresonator becomes smaller than about 50-100 nm, surface effects begin to have a significant effect on the bending rigidity, and consequently the resonant frequencies and the effective elastic modulus [67]. The surface stress effects will be described later in Section 4.3.…”
Section: Dynamics Of Micro/nanomechanical Resonatorsmentioning
confidence: 99%